Implementasi Kebijakan Pencegahan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkotika (P4GN) (Universitas 17 Agustus 1945 Surabaya, 2023)
The problem of drug abuse is a major problem faced by various countries, including Indonesia. The government is trying to overcome this problem through Presidential Instruction Number 12 of 2011 concerning the Implementation of Policies for the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) where one of the focuses is on the rehabilitation sector. This study aims to describe the implementation of the policy for the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) in the field of rehabilitation in South Jakarta City and all the factors that influence it. This research uses a descriptive method with a qualitative approach. The focus of this research is communication, resources, disposition, and bureaucratic structure. The data analysis technique was carried out by using interactive model data analysis. The results of this study indicate that the P4GN policy in the field of rehabilitation carried out by the South Jakarta BNNK has not been implemented properly and is not in accordance with the variable theory of policy implementation according to George C. Edward III. There are inhibiting factors such as a lack of human and budgetary resources, a lack of training for counselors, a lack of community information about rehabilitation, directions that change in the middle of implementation, and the implementation of Work From Home. However, the optimism for the success of the policy has received positive support through several supporting factors, including good communication between work units and implementing commitments, Anti-Drug Activists, and Community-Based Intervention activities.